2021
DOI: 10.3390/diagnostics11040628
|View full text |Cite
|
Sign up to set email alerts
|

ARG1 mRNA Level Is a Promising Prognostic Marker in Head and Neck Squamous Cell Carcinomas

Abstract: Head and neck squamous cell carcinomas (HNSCC) can be induced by smoking or alcohol consumption, but a growing part of cases relate to a persistent high-risk papillomavirus (HPV) infection. Viral etiology has a beneficial impact on the prognosis, which may be explained by a specific immune response. Tumor associated macrophages (TAMs) represent the main immune population of the tumor microenvironment with a controversial influence on the prognosis. In this study, the level, phenotype, and spatial distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…also found the same phenomenon ( 22 ). Macrophages are multifunctional plastic cells and are easily modulated by factors in the microenvironment which could promote them to polarize into M1 (antitumor type) or M2 type (pro-tumor type) ( 23 ). During tumor progression, macrophages usually transform into M2 type eventually, which may be related to a favorable prognosis of HPV + HNSCC ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…also found the same phenomenon ( 22 ). Macrophages are multifunctional plastic cells and are easily modulated by factors in the microenvironment which could promote them to polarize into M1 (antitumor type) or M2 type (pro-tumor type) ( 23 ). During tumor progression, macrophages usually transform into M2 type eventually, which may be related to a favorable prognosis of HPV + HNSCC ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…During tumor progression, macrophages usually transform into M2 type eventually, which may be related to a favorable prognosis of HPV + HNSCC ( 24 ). In breast cancer, gastric cancer, rectal cancer, and pancreatic cancer, survival analysis showed that low levels of M2 macrophage infiltration were associated with a better prognosis ( 23 ). Previous studies have shown that HPV + and HPV - HNSCC cell lines could induce macrophage polarization into M1 and M2 types, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARG1 (arginase 1) is a biomarker of M2 macrophages and has immunosuppressive and tumorigenic functions ( 44 ). The mRNA level of ARG1 has been demonstrated as an adverse prognostic factor for the OS of head and neck squamous cell carcinoma (HNSCC) patients ( 45 ). Furthermore, the relative expressions of another set of 16 immune-related genes (chemokines/cytolytic activity/immune checkpoints) in the TCGA cohort were investigated, and found that the expression level of CXCL9 increased significantly in the PAK7-MT group ( Figure 4B ) as compared to the PAK7-WT group.…”
Section: Resultsmentioning
confidence: 99%
“…The team focuses on molecular epidemiology of tumor viruses and developed several approaches to characterize the viral etiology of tumors [35][36][37]. Recently, the group is investigating tumor microenvironments with the aim to explain the prognostic advantage of patients with virally induced tumors and evaluate immune prognostic markers as well as therapeutic markers of small inhibitory molecules [38]. Furthermore, the group also develops tools for the analyses of viromes of both animals and humans and studies the interplay between the virome composition and infection of other pathogens on health and disease [39].…”
mentioning
confidence: 99%